2013
DOI: 10.1111/nph.12558
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol 3‐O‐rhamnoside‐7‐O‐rhamnoside is an endogenous flavonol inhibitor of polar auxin transport in Arabidopsis shoots

Abstract: Polar auxin transport (PAT) plays key roles in the regulation of plant growth and development. Flavonoids have been implicated in the inhibition of PAT. However, the active flavonoid derivative(s) involved in this process in vivo has not yet been identified. Here, we provide evidence that a specific flavonol bis-glycoside is correlated with shorter plant stature and reduced PAT.Specific flavonoid-biosynthetic or flavonoid-glycosylating steps were genetically blocked in Arabidopsis thaliana. The differential fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 58 publications
(118 reference statements)
8
120
0
Order By: Relevance
“…Flavonoids are repressors of auxin transport (27,28), and all three hybrids showed a down-regulation of genes involved in flavonoid biosynthesis ( Fig. 2 C and D), implying a reduction in flavonoid levels in the hybrids and presumably increased rates of IAA transport compared with the parental lines; the latter is confirmed for C24/Ler (26).…”
Section: The F1 Hybrids Show Alterations To Hormone-regulated Genes Andsupporting
confidence: 61%
See 1 more Smart Citation
“…Flavonoids are repressors of auxin transport (27,28), and all three hybrids showed a down-regulation of genes involved in flavonoid biosynthesis ( Fig. 2 C and D), implying a reduction in flavonoid levels in the hybrids and presumably increased rates of IAA transport compared with the parental lines; the latter is confirmed for C24/Ler (26).…”
Section: The F1 Hybrids Show Alterations To Hormone-regulated Genes Andsupporting
confidence: 61%
“…In the Arabidopsis hybrids, the increased auxin response mainly involves changes at the level of auxin biosynthesis involving repression of genes involved in producing the defense compounds, indole glucosinolates, and camalexin. Changes in flavonoid biosynthesis also contribute because flavonoids are negative regulators of polar auxin transport (27,28). Even moderate decreases in flavonoid biosynthesis gene expression improve plant growth (27).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonols and flavonoids such as quercetin were considered to inhibit auxin transporters (Brown et al, 2001), although later work suggested that flavonoids also act by redirecting PIN efflux protein localization (Santelia et al, 2008). Certain flavonoid mutants display auxin-related defects (Buer et al, 2013) and an auxin-transport inhibiting activity was recently assigned to the flavonol glycoside kaempferol 3-O-rhamnoside-7-O-rhamnoside (Yin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an Arabidopsis flavonoid 3-O-glycosyltransferase mutant, which overaccumulated kaempferol 3-O-rhamnoside-7-O-rhamnoside, showed reduced polar auxin transport (Yin et al, 2014). Similarly, auxin transport phenotypes in several Arabidopsis flavonoid mutants have been linked to altered accumulation of flavonoid glycosides as they contain undetectable levels of free kaempferol or quercetin aglycones (Buer et al, 2013).…”
Section: Flavonoids Rescue Nodulation In the Cre1 Mutantmentioning
confidence: 99%